Within‐island diversification in the land snail genus Formosana (Gastropoda, Clausiliidae) in Taiwan. (16th July 2022) - Hwang, Chung‐Chi; Ger, Mang‐Jye; Wu, Shu‐Ping
Abstract: The morphology‐based species delimitation of the land snail genus Formosana (Clausiliidae) was questioned, due to the high intraspecific variability and interspecific similarity of morphological characters. The systematics of Formosana from Taiwan are revised using molecular, morphological, and anatomical data. Phylogenies were constructed based on four mitochondrial and nuclear markers, by means of maximum likelihood and Bayesian inference analyses. Twelve valid and endemic species and subspecies were recognised from Taiwan, six of which are newly described herein: Formosana nanaoensis sp. n., Formosana hsuehshanensis sp. n., Formosana lilongshanensis sp. n., Formosana katipulensis sp. n., Formosana kaluluanensis sp. n., and Formosana tianchihensis sp. n. In addition, three nominal species are maintained as synonyms of earlier described species. A congener from China is transferred to the genus Formosanella as a new combination, Formosanella friniana com. n. The variability in morphological characteristics, and resulting difficulties for their taxonomic implication are critically discussed. Divergence time estimation and ancestral range reconstructions indicate that the Taiwanese Formosana most likely colonised in eastern Taiwan, approximately 4.7 million years ago in the Early Pliocene, and then differentiated into four major clades. The speciation events mainly occurred during the Late Pliocene and the Early Pleistocene. The biogeography and diversification of Formosana in Taiwan are discussed, in light of the concept of palaeoislands.